Chromosome Organization and Replisome Dynamics in Mycobacterium smegmatis - Isabella Santi (American Society for Microbiology, 2015)
ABSTRACT Subcellular organization of the bacterial nucleoid and spatiotemporal dynamics of DNA replication and segregation have been studied intensively, but the functional link between these processes remains poorly understood. Here we use quantitative time-lapse fluorescence microscopy for single-cell analysis of chromosome organization and DNA replisome dynamics in Mycobacterium smegmatis. We report that DNA replication takes place near midcell, where, following assembly of the replisome on the replication origin, the left and right replication forks colocalize throughout the replication cycle. From its initial position near the cell pole, a fluorescently tagged chromosomal locus (attB, 245° from the origin) moves rapidly to the replisome complex just before it is replicated. The newly duplicated attB loci then segregate to mirror-symmetric positions relative to midcell. Genetic ablation of ParB, a component of the ParABS chromosome segregation system, causes marked defects in chromosome organization, condensation, and segregation. ParB deficiency also results in mislocalization of the DNA replication machinery and SMC (structural maintenance of chromosome) protein. These observations suggest that ParB and SMC play important and overlapping roles in chromosome organization and replisome dynamics in mycobacteria. IMPORTANCE We studied the spatiotemporal organization of the chromosome and DNA replication machinery in Mycobacterium smegmatis, a fast-growing relative of the human pathogen Mycobacterium tuberculosis. We show that genetic ablation of the DNA-binding proteins ParB and SMC disturbs the organization of the chromosome and causes a severe defect in subcellular localization and movement of the DNA replication complexes. These observations suggest that ParB and SMC provide a functional link between chromosome organization and DNA replication dynamics. This work also reveals important differences in the biological roles of the ParABS and SMC systems in mycobacteria versus better-characterized model organisms, such as Escherichia coli and Bacillus subtilis.